Ergonomics and Business Policies for the Promotion of Well-Being in the Workplace - Montoya-Reyes, Mildrend (IGI Global, 2022)
In recent years, employee health and well-being have been of increasing importance to companies as they attempt to move toward more sustainable business models and futures. Taking health into account in business policies helps ensure sustainable production systems. The role of ergonomics in companies can contribute to creating a more sustainable work environment, which accelerates the performance of the organization and promotes professional development, impacting the health and well-being of workers in a broad and positive way. Ergonomics and Business Policies for the Promotion of Well-Being.